Nutrient transfer and antioxidant effect of adzuki bean before and after GABA enrichment - Jiang, Xiujie; Xu, Qingpeng; Zhang, Jiayu; Li, Zhijiang; Tang, Huacheng; Cao, Dongmei; Zhang, Dongjie (Frontiers in Nutrition, 2023)
Based on the process optimization and synthesis mechanism of GABA enrichment in early adzuki bean germination, the transfer of nutrients before and after GABA enrichment in adzuki bean germination under vacuum combined with MSG stress was studied by means of chromatography and scanning electron microscope, and the antioxidant activity effect of different solvent extracts before and after adzuki bean germination were evaluated by in vitro experiments.The results showed that the nutritional characteristics of adzuki bean rich in GABA changed significantly (P < 0.05), the total fatty acids decreased significantly (P < 0.05), and the 21 amino acids detected increased significantly(P < 0.05). After germination, the starch granules of adzuki bean became smaller and the surface was rough germination stress significantly increased the antioxidant activity of the extracts from different solvents (P < 0.05), and the water extracts had the best effect on DPPH and ·OH radical scavenging rates of 88.52% and 83.56%, respectively. The results indicated that the germinated adzuki bean rich in GABA was more nutritious than the raw adzuki bean and had good antioxidant activity in vitro.